Pengaruh Dana Zakat Terhadap Jumlah Penduduk Miskin Jawa Timur - Firmansyah, Mochamad; Ajib Ridlwan, Ahmad (Universitas Negeri Surabaya, 2019)
The proverty is a problem that has not been resolved to date. This study aims to determine the effect of zakah on the poor people number in East Java. This research is quantitive research. Data analysis techniques using simple linear regression analysis. The results showed that the zakah collected and distributed by the East Java’s BAZNAS had an influence on the poor people number in East Java.